Understanding the Performance of a Nanocomposite Based on a Conjugated Azo-Polymer and Reduced Graphene Oxide with Photoelectrically Switchable Properties by Analyzing the Potential Profile during Photocurrent Generation - Pacheco, Jéssica Crivelaro [UNESP]; Olean-Oliveira, André [UNESP]; Teixeira, Marcos F. S. [UNESP] (Wiley, 2020)
This work describes the photoelectrochemical properties of devices coated with poly(azo-Bismarck Brown R) and the nanocomposite poly(azo-Bismarck Brown R)/reduced graphene oxide. Chronoamperometric methods with pulsed light are applied to the polymer surfaces of poly(azo-Bismarck R) and poly(azo-Bismarck Brown R)/rGO nanocomposites at two applied potentials (corresponding to the reduced and oxidized polymer forms) to obtain information on the photocurrent in a short response time. The results indicate that the photoactivity of the nanomaterial depends on the oxidation state of the azo-polymer and its chemical structure. The carrier mobility of the material is affected by the applied potential profile and consequently by the isomerism of the polymer backbone. This behavior explains the photoelectrochemical performance of the nanocomposite material. The photoresponsiveness of the semiconducting hybrid material with light-switchable conductance is promising for applications in photoelectrochemical switches and molecular switching devices.
Keywords: 2D layered materials; conducting polymer; driven-light; nanocomposite; resistive switching properties